Corrosive induced esophageal and gastric injury: Histopathological evaluation of surgically resected specimens over a decade in a tertiary care center - Jimil Shah; Anuraag Jena; Shweta Shweta; Kim Vaiphei; Vikas Gupta; Naveen Kumar; Anupam K Singh; Rakesh Kochhar (Indian Journal of Pathology and Microbiology)
Background: Caustic ingestion is associated with long-term sequelae like esophageal stricture, gastric cicatrization, and long-term risk of dysplasia or even carcinoma. However, only a few small studies have explored histopathological aspects of caustic-induced esophageal/gastric injury. Materials and Methods: We retrospectively evaluated specimens of patients undergoing surgery due to caustic ingestion-related complications from 2008 to 2020. Pathological examination was conducted by two independent gastro-pathologists to evaluate the extent and depth of the caustic injury, presence or absence of tissue necrosis, type and degree of inflammation, or presence of any dysplastic cells. Results: A total of 54 patients underwent surgical exploration during the inclusion period and complete details of 39 specimens could be retrieved. The mean age of the included patients was 28.66 ± 9.31 years and 25 (64.1%) were male. The majority of patients (30; 76.9%) had a history of caustic ingestion more than three months before the surgery and the presence of long or refractory stricture was the most common indication for the surgery (20; 51.28%). In the resected specimen, a majority of patients had superficial esophageal or gastric ulcer (90.6%; 60.0%), transmural inflammation (68.8%; 65.6%), transmural fibrosis (62.5%; 34.4%), and hypertrophied muscularis mucosa (78.13%; 53.3%). However, none of the patients had dysplasia in the resected esophageal or gastric specimens. Conclusion: Caustic ingestion leads to mucosal ulceration, transmural inflammation, and transmural fibrosis which might be the reason for refractory stricture in such patients.